The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/microorganisms10010164
|View full text |Cite
|
Sign up to set email alerts
|

It Works! Organic-Waste-Assisted Trichoderma spp. Solid-State Fermentation on Agricultural Digestate

Abstract: This study aimed at valorizing digestate through Trichoderma spp. solid-state fermentation (SSF) to produce a potentially ameliorated fertilizer combined with fungal biomass as a value-added bioproduct. Plant-growth-promoting Trichoderma atroviride Ta13, T. reesei RUT-C30, T. asperellum R, and T. harzianum T-22 were tested on different SSF substrates: whole digestate (WD), digestate dried up with wood sawdust (SSF1), and digestate enriched with food waste and dried up with wood sawdust (SSF2). The fungal bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…The previous results about the aptitude of digestate mixed with agro-industrial wastes to serve as a substrate for fungal growth were so confirmed and extended also to the production of enzymes and metabolites.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The previous results about the aptitude of digestate mixed with agro-industrial wastes to serve as a substrate for fungal growth were so confirmed and extended also to the production of enzymes and metabolites.…”
Section: Discussionmentioning
confidence: 55%
“…The mycelial mass was quantified using the standard curve method as described by Alias et al . Briefly, 5 g of homogenized fermented substrate was collected at 0, 3, 6, 13, 20, 27, and 34 days after inoculation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be mentioned that India cultivated in 2016 approximately 43.19 million hectares of rice producing 280 million tons of wastes (Sarangi et al, 2021). Moreover, the European countries produce 180 million tons of wastes yearly via biogas production (Alias et al, 2022). Since the agricultural wastes as rice straw contain cellulose, hemicellulose and lignin, therefore this makes it difficult to degrade (Kaur et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…One contribution [ 5 ] evaluates digestate valorisation through fungal solid-state fermentation to produce an ameliorated biofertiliser as a value-added product. Brémond et al [ 6 ] evaluate the efficacy of digestate post-treatment with isolated ligninolytic aerobic consortia in increasing methane recovery during recirculation.…”
mentioning
confidence: 99%